'My Future Son is Possibly Alive'. Existential Presupposition and Empty Terms in Abelard's Modal Logic. Issue 4 (2nd October 2018) - Binini, Irene
Abstract : The aim of this paper is to investigate the problem of existential import in Abelard's modal logic, and to ask whether the system of logical relationships that he proposes for modal propositions maintains its validity when some of the terms included in these propositions are empty. In the following, I first argue that, just as in the case of non-modal propositions, Abelard interprets modal propositions as having existential import, so that it is a necessary condition for the truth of propositions like 'It is possible for my son to be alive' or 'it is necessary that all men are animals' that their subjects' referents exist. Then, I present the schemata of inferences that Abelard proposes to describe the logical behaviour of de rebus modal propositions. I argue that these systems of relations are valid only as long as all the terms contained in the formulas have an existing referent. I also claim that Abelard was aware of this difficulty (at least in the Logica Ingredientibus ), and, accordingly, he explicitly decided to restrict the validity of his modal system to propositions that do not contain empty terms.